Disinfection Performance against Salmonella Typhi in Water by Radio Frequency Inductive Couple Plasma System - Desmiarti, Reni; Hazmi, Ariadi; Li, Fusheng (ITB Journal Publisher, LPPM ITB, 2017)
The disinfection performance of the radio frequency inductively coupled plasma (RFICP) system against Salmonella Typhi in water was examined using continuous flow experiments. The evaluation was based on disinfection efficiency, death rate constant, disinfection yield, and energy consumption. For all experiments the electromagnetic flux generated in the plasma reactor varied from 4 to 6 W/cm2. The disinfection efficiency and death rate constant of Salmonella Typhi decreased with the increase of the initial number of Salmonella Typhi bacteria. The disinfection yield increased from 784 to 1889 CFU/KWh and the energy consumption decreased from 0.28 to 0.07 KWh/L with the flowrate increasing from 5 to 20 mL/minute. The flowrate is an important parameter in predicting disinfection performance against pathogenic bacteria in water to design drinking water treatment plants.